Keragaman Karakter Kualitatif Generasi M1 Kedelai Hitam Varietas Detam 1 Hasil Iradiasi Benih dengan Sinar Gamma - Siti Aisah; Isnaini Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This research was conducted to determine the effect of gamma ray irradiation doses in increasing the qualitative character variability of M1populastion of Detam-1variety. Selected seed with the germination rate of more than 90% was irradiated at the BATAN Isotop Laboratory in Jakarta, which consists of 4 levels, that isG1 (100 Gy gamma ray), G2 (150 Gy gamma ray), G3 (200 Gy gamma ray), G4 (250 Gy gamma ray) and Detam-1 as a control parent.Evaluation of M1 generation was established by planting M1 seed at the Faculty of Agriculture Experiment Station, University of Riau during May to August 2018 usinga completely randomized design with 4 replications.From the individual plants in the field trial plots, it was observed that the qualitative characters included observations of leaves, flowers, stems and pods. Data from the results of analysis were then analyzed for diversity using program Ms. Excel.Gamma ray irradiation changed in some qualitative characters such as, created white leaf color, two-leaflet and four-leaflet leaves in the rate of 150 Gy and five-leaflet leaves in the rate of 200 Gy. Keywords:soybean, diversity, gamma ray, qualitative characters